Constitutional Regulation and Practical Realization of powers’separation in the Russian Federation - Rakitskaya, Elena Aleksandrovna Kremyanskaya, Yuri Ivanovich Leibo, Evgeniu Yakovlevich Pavlov, Inna Alexandrovna; Kuznetsova, Tamara Olegovna (Opción, 2019)
This article is devoted to the system of separation of powers, which was first created and analyzed by 18 century philosophers and implemented in modern democratic countries. The methodological basis of the article is formed by general scientific and special methods of investigation into legal phenomena. As a result, review of constitutional status of three branches is not possible without deep analysis of the forms of mutual control. The authors concluded, the system of separation of powers is constitutionally regulated and established in practice permitting to prevent power from usurpation and assisting state developing in a democratic way.